Crustal structure and deformation mechanism of the western northeast Tibetan Plateau - Wang, Zining; Xiong, Xiaosong; Wu, Guowei; Li, Zhichao; Ye, Zhuo; Jin, Zhongyuan (Frontiers in Earth Science, 2023)
The collision between the Indian and Eurasian plates continues to drive significant deformation and uplift within the interior of the Tibetan Plateau, together with its outward expansion along the margins. In particular, the North Qilian Shan fold-thrust belt (NQLS) and the Hexi Corridor basins (HXBS) represent the northernmost region of the northeastern Tibetan Plateau. This area serves as a natural laboratory for deciphering mechanisms of crustal deformation and thickening along the plateau’s margins. Specifically, the northeastern Tibetan Plateau has been attributed to 1) southward underthrusting of the Asian lithosphere, 2) distributed shortening and crustal thickening, 3) vertical inflation of the Tibetan crust due to mid-lower crustal channel flow, and 4) intracontinental subduction facilitated by large-scale strike–slip faults. The exact mechanism underlying the most concentrated convergent stress in the western segment of NQLS–HXBS remains a subject of debate. To address this uncertainty, we gathered seismic data along a 130-km-long linear array that extends northward from NQLS, traversing the Jiuquan Basin and reaching the Huahai Basin. Our analysis, conducted through the receiver function method, reveals intriguing findings. The Moho depth deepens from 45–50 km beneath the Huahai Basin to 55–60 km beneath NQLS. Notably, a double Moho structure emerged, marked by a distinctive near-flat positive amplitude at a depth of 45–50 km beneath NQLS within a distance of 0–50 km. Our study presents a comprehensive analysis of the crust-scale deformation mechanism, shedding light on the following key aspects: 1) the development of a decollement at 12–20 km depth decoupling the upper and lower crust; 2) deformation of the upper crust occurring through south-dipping brittle thrust faults, while the lower crust features imbricate structures and duplexes; 3) evidence pointing to the underthrusting of the Beishan Block beneath NQLS, indicated by the double Moho beneath NQLS; and 4) the formation of a Moho ramp beneath the Jiuquan Basin, facilitating the transfer of shortening stress from beneath NQLS and HXBS to the north. In the context of the western segment of NQLS and HXBS, our speculation is that coupled distributed shortening and Beishan Block subduction beneath NQLS work in tandem to accommodate crustal deformation.